PENINGKATAN AKTIVITAS DAN HASIL BELAJAR AKUNTANSI MATERI LAPORAN KEUANGAN MELALUI METODE GALLERY WALK DUATI-DUATA - Mariyaningsih, Nining (Dinamika Pendidikan, 2014)
In learning accounting, conventional learning models are still frequently used by the teacher. As a result, the learning become monotonous and itâs not maximum. The problem of this study is wheather through Gallery Walk Duati-Duata can improve the activity and learning outcomes of accounting students.This study was class action research which was designed into two main cycles. Each cycle consisted of four stages started from planning, acting, observing and reflecting. The result showed that : (1) Learning activities increase from 27,78% before cycle, 69,45% in first cycle and 93,88% in second cycle, (2) The learning outcomes increase, from 22,22% before siklus, 75% in first cycle and 94,44% in second cycle. Therefore the use of this methods could be one of the reference of teachers in implementing the learning process.